Detecting Signs of Depression in Portuguese Texts Considering Brazil’s Cultural and Regional Aspects Using LLMs - Rodrigues, Leidiane; Fernandes, Deborah; Lago, Marilúcia (Companion Proceedings of the Brazilian Symposium on Computing Applied to Healthcare (SBCAS); 2025: Companion Proceedings of the 25th Brazilian Symposium on Computing Applied to Health, 2025)
This study investigates the identification of depression traits in messages from the social network Reddit, focusing on young people and adolescents. To this end, two lexicons were compared: one with terms in Portuguese without cultural expressions and another culturally enriched lexicon, constructed from Brazilian song lyrics. Using the GPT 3.4 and Flash 1.5 models, we analyzed messages labeled as depressive and non-depressive, classified by a mental health specialist. The results show that the cultural adaptation of the lexicon allowed a more sensitive and accurate analysis, suggesting the importance of regional lexicons to improve the detection of signs of depression in specific cultural contexts.